Quantitative Plate Tectonics: Physics of the Earth - Plate Kinematics – Geodynamics - Schettino, Antonio (Springer, 2016)
This textbook on plate tectonics is designed for students in geology and geophysics to acquire in-depth knowledge of quantitative methods in plate kinematics and dynamics. Quantitative Plate Tectonics can also be used as a reference book by geoscientists who desire to expand their knowledge beyond their own specialization, or by oil-and-gas professionals and ore deposit specialists that need to investigate the geodynamic context of formation of geologic resources. Finally, this book can be considered as a comprehensive monograph on plate tectonics, which addresses the different quantitative aspects of this broad discipline, which has been traditionally partitioned into separate or quasi-separate branches.